Identifiying the PID-N method performance for speed control of BLDC motor propeller on catamaran ships model - Setiawan, Budhy; Firdaus, Mohammad Kamil; Wibowo, Sapto; Agafta, Ian; Zain, Fikri (Eastern-European Journal of Enterprise Technologies, 2023)
Some archipelagic countries must have wide sea. This condition means that there is transportation of goods and people problem. Therefore, an effort has been made to explore renewable energy especially solar energy. In this research, a BLDC (Brush Less Direct Current) motor propeller is applied, and PID-N (Proportional, Integral, and Derivative – Filter Coefficient) method for Catamaran ship speed control. Where PID-N has additional filters such as P, I, and D; however, the advanced performance of this control uses RLS (Recursive Least Square) actuator modeling is the most systematical and flexible design. The experiment includes the speed response of ships with payload and without payload, as well as changes in speed settings. The results show that the ship's speed control using the PID-N has smooth and definite speed control. The PID-N design is systematical, easy and quick for the control designer to change the actuator or sensor performance, if there will be any actuator or sensor replacement with different specifications, which is required in commercial. As it is known, in commercial design, time and method are crucial and has to be effective. The PID-N control method shows its superiority. In detail, the Catamaran speed setting is incremented from 0.4 m/s to 0.6 m/s without payload, the average settling time is 6 seconds with the average error speed 0.071 m/s in the set speed 0.6 m/s. For setting speed increased by 0.4 m/s to 0.6 m/s with payload, settling time gets longer, 7 to 13 seconds with the average error speed 0.01 m/s in the set speed 0.06 m/s. It performs small errors and fasts settling time. The ship model has experimented on an artificial pond, it is related to the proportional small sea wave. The research also shown the ratio of electric power consume toward speed setting is in exponential formula